Dziedzictwo kompleksów. Kulturowa klęska Kresów? - Łozowska, Katarzyna R. (Studia Etnologiczne i Antropologiczne, 2012)
The borderlands perceived as borderlines, peripheries, a small homeland form a discourse of multiculturalism, one of the strongest discourses successfully functioning in the light of others, an anthropological, sociological or historical one nowadays. It was 1989 that made us aware of not only rich traditions of what was traditionally called the borderlands, but confronted Poles with the existence of the “Other” and “Foreign”, as well as discovered a series of relations that joined us with them. The awareness of cultural, social and traditional differences slowly overlapped with a belief that the freedom of Poland is not only the result of their dedicated battle, and martyrdom inscribed into our patriotic genotype. Apart from pride, Poles strongly felt the sense of injustice for territorial, cultural and economic loss, unjust accusations of our neighbours, but also a hidden sense of guilt, Poles’ co‑responsibility for the Holocaust or our colonization past. A discourse of multiculturalism is considered to be the product of passion and power, needs, anxieties, projects and longings. Searching joint experiences with our neighbours, we establish our existence according to the latest biding criteria. We use politics to hear “Polishness” when saying “multiculturalism”. A multicultural pot included accusations of xenophobia and arguments against it, our openness to the “Other”, tolerance of various ethnoses, joint historical experiences. Multiculturalism is an answer to Jews’, Lithuanians’, Ukrainians’ or Germans’ grudges telling their own history in a way totally different from our versions. Collapsing borderland projects discover a new space of multivoicing, without ideological benefits for the Polish culture. The problem of the “Other” is becoming a suggestion to find a real self, deprived of an embarrassing heritage and „overload of everyday life” in its face.